The INDEPTH standard population for low- and middle-income countries, 2013 - Osman Sankoh; David Sharrow; Kobus Herbst; Chodziwadziwa Whiteson Kabudula; Nurul Alam; Shashi Kant; Henrik Ravn; Abbas Bhuiya; Le Thi Vui; Timotheus Darikwa; Margaret Gyapong; Momodou Jasseh; et al. (Taylor & Francis Group, 2014)
Crude rates such as the crude death rate are functions of both the age-specific rates and the age composition of a population. However, differences in the age structure between two populations or two time periods can result in specious differences in the corresponding crude rates making direct comparisons between populations or across time inappropriate. Therefore, when comparing crude rates between populations, it is desirable to eliminate or minimize the influence of age composition. This task is accomplished by using a standard age structure yielding an age-standardized rate. This paper proposes an updated International Network for the Demographic Evaluation of Populations and Their Health (INDEPTH) standard for use in low- and middle-income countries (LMICs) based on newly available data from the health and demographic surveillance system site members of the INDEPTH network located throughout Africa and southern Asia. The updated INDEPTH standard should better reflect the age structure of LMICs and result in more accurate health indicators and demographic rates. We demonstrate use of the new INDEPTH standard along with several existing 'world' standards and show how resulting age-standardized crude deaths rates differ when using the various standard age compositions.